Provably secure certificate less blind proxy re-signatures - Tao FENG; Yi-xin LIANG (Tongxin xuebao)
Using bilinear groups,an efficient certificate less blind proxy re-signature scheme was proposed based on the proxy re-signature scheme and blind signature scheme.The scheme solves the using of certificate in certificate-based scheme and removes key escrow in ID-based scheme.While achieving message privacy features of the proxy signature conversion.Based on the difficulty of NGBH and Many-NGBH problem,It proves that the new scheme can resist forgery attack characteristics.The scheme satisfies security properties:correctness and message blindness.